2017
DOI: 10.1016/j.paid.2016.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural comparative examination of the Academic Motivation Scale using exploratory structural equation modeling

Abstract: Acknowledgements:We are grateful for Fruzsina Lukács, József Salamon, and János Salamon for the data gathering. Highlights The factor of the Academic Motivation Scale (AMS) was assessed.  Hungarian and French high school and university students participated.  Exploratory structural equation modeling (ESEM) supported the 7-factor model.  The AMS was reliable based on three different indices.  Gender invariance was high, age-and language invariances were low. Abstract The goal of the present research was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
2
16
0
2
Order By: Relevance
“…Besides the seven-factor structure, the CFA results of some studies confirmed the five-factor structure corresponding to SDT (Can, 2015;Liu et al, 2017;Stover et al, 2012;Tóth-Király et al, 2017). This structure consisted of AM, ER, INR, IDR and intrinsic motivation that includes items from IMTK, IMTA, IMTE.…”
Section: Factorial Validitymentioning
confidence: 68%
See 1 more Smart Citation
“…Besides the seven-factor structure, the CFA results of some studies confirmed the five-factor structure corresponding to SDT (Can, 2015;Liu et al, 2017;Stover et al, 2012;Tóth-Király et al, 2017). This structure consisted of AM, ER, INR, IDR and intrinsic motivation that includes items from IMTK, IMTA, IMTE.…”
Section: Factorial Validitymentioning
confidence: 68%
“…The AMS has been adapted and validated with diverse samples in different cultural contexts including Canada (Grouzet, Otis, & Pelletier, 2006;Guay, Morin, Litalien, Valois, & Vallerand, 2015;Vallerand, Blais, Brière, & Pelletier, 1989;Vallerand et al, 1992Vallerand et al, , 1993, the United States (Cokley, 2000(Cokley, , 2015Cokley, Bernard, Cunningham, & Motoike, 2001;Fairchild et al, 2005;Liu, Ferrell, Barbera, & Lewis, 2017;Osei Akoto, 2014;Smith, Davy, & Rosenberg, 2010, 2012, Brazil (Davoglio, Santos, & Lettnin, 2016;Stover, de la Iglesia, Boubeta, & Liporace, 2012), Chile (Orsini et al, 2015), Poland (Ardeńska et al, 2016), Hungary (Tóth-Király et al, 2017), Greece (Barkoukis, Tsorbatzoudis, Grouios, & Sideridis, 2008;Tsorbatzoudis, Barkoykis, & Grouios, 2001), Norway (Støen Utvaer & Haugan, 2016), France (Tóth-Király et al, 2017), Spain (Burgueño et al, 2017), Slovenia (Puklek Levpušček & Podlesek, 2017), Turkey (Ardeńska et al, 2016;Aydin, Yerdelen, Gürbüzoğlu Yalmanci, & Göksu, 2014;Can, 2015;Cavusoglu & Karatas, 2015;Haslofça & Korkmaz, 2016;Karaguven, 2012) and Italy (Alivernini & Lucidi, 2008). Specially, the AMS was also adapted with Asian samples in Malaysia (Chong & Ahmed, 2012), Singapore (Caleon et al, 2015;…”
Section: Previous Studies On Adaptation and Validation Of The Amsmentioning
confidence: 99%
“…The AMS has been translated into many different languages: Greek (Barkoukis et al, 2008), Italian (Aliv-ernini & Lucidi, 2008), Turkish (Karagüven, 2012), Spanish (Stover et al, 2012) German (Wilkesmann et al, 2012), Romanian (Maican & Lixandroiu, 2015), Spanish (Orsini et al, 2015), Hungarian (Tóth-Király et al, 2017). However, the Polish version has never been appropriately adapted and validated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used by researchers in many countries and in various educational contexts (e.g. Cokley, Bernard, Cunningham, & Motoike, 2001;Fairchild, Horst, Finney, & Barron, 2005; Barkoukis, Tsorbatzoudis, Grouios, & Sideridis, 2008;Alivernini & Lucidi, 2008;Faye & Sharpe, 2008;Komarraju, Karau, & Schmeck, 2009;Horyna & Bonds-Raacke, 2012;Karagüven, 2012;Stover, de la Iglesia, Boubeta, & Liporace, 2012;Wilkesmann, Fischer, & Virgillito, 2012;Guay, Ratelle, Larose, Vallerand, & Vitoro, 2013;Maican & Lixandroiu 2015;Orsini et al, 2015;Tóth-Király et al, 2017;Litalien et al, 2017). The AMS is based on seven-factor structure: amotivation, three types of extrinsic motivation and three types of intrinsic motivation.…”
Section: Introductionmentioning
confidence: 99%
“…12) Seu progresso para uma vida mais saudável (pense sobre fumo, álcool, dieta, exercício etc. ), como você cuida da sua saúde: O processo de tradução e validação psicométrica foi desenvolvido com base na metodologia recomendada pela literatura nacional e internacional (BEATON et al, 2000;FERRER et al, 1996;GUILLEMIN;BOMBARDIER;BEATON, 1993;PASQUALI, 1999), a qual tem sido utilizada por vários autores (AMUNDSEN et al, 2017;CUKLJEK;JURESA;BABIC, 2017;LENFERINK et al, 2016;SCHULZE et al, 2017;TÓTH-KIRÁLY et al, 2017;WANG et al, 2017). No nosso estudo, a sequência das etapas inseridas no processo de adaptação cultural foi aquela proposta e testada em outros estudos realizados por pesquisadores do Grupo de Investigação em Reabilitação e Qualidade de Vida (GIRQ), do qual também fazemos parte (ASSUNÇÃO et al, 2013;CALTRAN, 2016;CUNHA, 2016;FREITAS, 2016;SOUZA E SILVA;CIOL, 2013;PELEGRINO et al, 2012).…”
Section: Resultados Relacionados àS Análises Descritivas E Da Validaçunclassified